2011
DOI: 10.1063/1.3615712
|View full text |Cite
|
Sign up to set email alerts
|

A thin metal sheath lifts the EH to HE degeneracy in the cladding mode refractometric sensitivity of optical fiber sensors

Abstract: The effective indices of the cladding modes of optical fibers depend on the refractive index of the medium surrounding the fiber. We show experimentally and theoretically that while cladding modes with similar effective indices normally have similar refractometric sensitivities, the addition of a 50 nm thick gold sheath enhances the sensitivity of some EH modes by more than one order of magnitude while nearly completely suppressing the sensitivity of neighbouring HE modes (by three orders of magnitude, down to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 13 publications
7
45
0
Order By: Relevance
“…corresponding to the left of the SPR signature) is the most sensitive. This observation is consistent with our researches made on bulk refractometry [13]. Fig.6a, no ut 488 nm was (Fig.6b).…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…corresponding to the left of the SPR signature) is the most sensitive. This observation is consistent with our researches made on bulk refractometry [13]. Fig.6a, no ut 488 nm was (Fig.6b).…”
Section: Resultssupporting
confidence: 95%
“…Thanks to this linear polarizer, we are able to optimize the SPR signature in the amplitude spectrum of the TFBG by maximizing the coupling of the cladding modes to the SPR. This is achieved when light is polarized parallel to the fiber surface (mode p, as explained in [13]). The monitoring of the SAM's formation is observed with the optical vector analyzer.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…We showed that narrowband resonant features (also located at wavelengths just below the SPR center) present a wavelength shift that enables refractive index measurements with a resolution better than 10 -5 RIU, achieved through a quality factor of 10 5 and signal-tonoise ratio greater than 50 dB [13,14]. This particular finding was supported by a recent theoretical analysis that showed how the presence of the gold layer shields azimuthally polarized cladding modes from the outside environment while allowing radially polarized ones to tunnel through and excite Plasmons [15]. Fig.…”
Section: Gold-coated Tfbgssupporting
confidence: 66%
“…An unambiguous SPR signature appears in the TFBG amplitude spectrum, as reported in [11,12]. It is strongly sensitive to surrounding refractive index (SRI) changes [12][13][14][15], which yields an implementation of SPRbased (bio-)sensors easy to fabricate and to use.…”
Section: Introductionmentioning
confidence: 92%
“…However, a prism-based SPR configuration has a number of disadvantages, such as bulky size and complex operation and in addition real time/remote sensing is difficult to implement. In order to overcome these disadvantages, SPR-based optical fiber sensors have attracted significant interest [6][7][8][9]. A fiber based sensing configuration allows for a compact sensing element and sample volume, the capacity for remote sensing and the potential for disposable miniaturized sensing devices.…”
Section: Introductionmentioning
confidence: 99%